Cardiovascular risk assessment and preventive activities associated factors among women nurses in Hospital Universiti Sains Malaysia - Siti Norazlina Juhari (2017)
Introduction: Cardiovascular diseases are the leading cause of death and disability among both women and men globally, including Malaysia and are projected to leading cause of death up to 2030. Lifestyle cardiovascular risks such as dietary habits, physical activities, and smoking are fundamental components in preventive cardiovascular activities and deflected to blood pressure, level of blood lipid, level of blood sugar, BMI that contribute development of cardiovascular disease. Objectives: To determine the rate of moderate to high CVD risk and preventive activities associated factors and association between shift work with cardiovascular risk among women nurses in Hospital Universiti Sains Malaysia. Methadology: This cross sectional study was done among women nurses who are working in Hospital Universiti Sains Malaysia. A structured question derived from WHO STEPs questionnaire was used as study tool. Cardiovascular screening of blood pressure, blood glucose, serum lipids and BMI measurement were done for each participants. Cardiovascular risk assessment were done based on Framingham Coronary Disease Risk prediction score (FRS). Findings : A total of 202 women nurses were involved in this study. The cardiovascular disease risk of moderate to high and low were 33.2% and 66.8% respectively based on Framingham Coronary Disease Risk prediction. Physical activities (adjusted odds ratio of 3.36,95% confidence interval (CI) 1.70-6.64, p<O.OOI), dietary habit (adjusted odds ratio of 16.87,95% CI 3.84-74.39, p<O.OOI), screening ofDM (adjusted odds ratio of3.59, 95% CI 1.81-7.10, p<O.OOI) and shiftwork (adjusted odds ratio of9.85, 95% CI 4.71-20.60, p<O.OOI) were significantly associated with moderate to high cardiovascular disease risk. Conclusion: Measures needed to be done to promote appropriate healthier diet and healthy lifestyle activities. Promotion of healthy lifestyle should be a fundamental action of primary care in disease prevention.